2009
DOI: 10.1002/zaac.200900304
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Synthesis, Crystal Structure and Thermal Stability of two 3d‐4f Heterometallic Coordination Polymers

Abstract: Two new 3d‐4f heterometallic coordination polymers, [LnCu(nic)2(ox)]·2H2O (Ln = Sm(1), Dy (2), ox = oxalate anion, Hnic = nicotinic acid) were synthesized and characterized by elementary analysis, IR spectroscopy and thermogravimetric analysis, as well as single‐crystal X‐ray diffraction. The two structures exhibit the same unusual 3D microporous heterometallic coordination frameworks with 13.7 % voids occupied by guest water molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A pyridinecarboxylic acid (nicotinic or isonicotinic acid) is a fascinating ditopic linker, as it contains two different donor groups: a pyridine N atom and two carboxylic O atoms. When these linkers are allowed to join the heterometallic nodes, a selectivity of coordination of the donor N and O atoms can occur, as their preferences for metal centers are different. However, this selectivity has been tested only for one dinuclear lanthanide–transition metal (3d–4f) node and it has been found that the carboxylic acid groups coordinate to the hard, oxophilic lanthanide ion, whereas the N atom binds to the transition-metal ion as expected . As far as is known, to date there has been no study on how the linking is controlled when heterometallic 3d–3d′ nodes are joined by such spacers.…”
Section: Introductionmentioning
confidence: 99%
“…A pyridinecarboxylic acid (nicotinic or isonicotinic acid) is a fascinating ditopic linker, as it contains two different donor groups: a pyridine N atom and two carboxylic O atoms. When these linkers are allowed to join the heterometallic nodes, a selectivity of coordination of the donor N and O atoms can occur, as their preferences for metal centers are different. However, this selectivity has been tested only for one dinuclear lanthanide–transition metal (3d–4f) node and it has been found that the carboxylic acid groups coordinate to the hard, oxophilic lanthanide ion, whereas the N atom binds to the transition-metal ion as expected . As far as is known, to date there has been no study on how the linking is controlled when heterometallic 3d–3d′ nodes are joined by such spacers.…”
Section: Introductionmentioning
confidence: 99%